Change in physiological variables in the last 2 weeks of life: An observational study of hospital in-patients with cancer. (February 2015) - Taylor, Paul; Crouch, Simon; Howell, Debra A; Dowding, Dawn W; Johnson, Miriam J
Background: Recognising dying remains a difficult clinical skill which has gained increasing importance in the United Kingdom since the Neuberger review. Clinical and research methods exist to aid recognition of dying but do not exhibit the level of accuracy required for such an important decision. Aim: To explore change in key clinical parameters as cancer patients near the end of life. Design: This is a retrospective cohort study of terminally ill patients. Data were collected from hospital case-notes. Case-note data were analysed using multilevel modelling to explore absolute values and rates of change of given variables. Setting/participants: Hospital in-patients who died from solid-tumour malignancies within a 3-month period in 2009 formed the cohort. The setting was an acute hospital trust in the North of England. Results: A total of 15, 337 data points from the case-notes of 102 patients were analysed. There was a clinically and statistically significant deterioration in respiratory function and renal function over the last 2 weeks of life. Heart rate and serum sodium also changed but did not vary greatly from normal limits. White cell parameters, haemoglobin and albumin showed evidence for change over longer periods. Conclusion: Results demonstrate statistically and clinically significant change in routinely measured respiratory and renal function variables during the final 2 weeks of life in people dying with cancer. Although useful in acute early warning scores, in a terminally ill patient, relative haemodynamic stability should not be interpreted as reassuring. Further work is needed to understand how these findings apply to the individual or inform other prognostic work.